The PENGARUH KECERDASAN EMOSIONAL, MANAJEMEN KONFLIK, DAN KOMPETENSI TERHADAP PERILAKU KERJA GURU PADA SMP SWASTA DI KOTA YOGYAKARTA - Nur Fitri Melasari; Surya Darmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study empirically examines the effects of emotional intelligence, conflict management, and competence on teacher work behavior in private junior high schools, aiming to identify the most influential direct drivers of teacher performance. A quantitative cross-sectional design was employed. Primary data from 90 teachers at private Junior High School’s in Yogyakarta, selected via purposive sampling, were collected through online questionnaires and analyzed using PLS-SEM, including outer model, inner model, and hypothesis testing. The results reveal that emotional intelligence exerts a positive yet statistically non-significant effect on teacher work behavior. Conversely, conflict management and competence demonstrate a positive and significant effect. These findings confirm that teacher work behavior is more robustly enhanced by the capacity to manage interpersonal conflicts effectively and by thorough mastery of professional competencies spanning planning, implementation, and evaluation than by emotional intelligence alone. The hypotheses regarding conflict management and competence are thereby supported. The findings suggest that school management should prioritize strengthening conflict management and professional competency development. However, the cross-sectional design precludes causal inferences, and the limited variable scope restricts generalizability and omits other potential exogenous factors beyond the current model